Peran BMT Raudhah dalam Pengembangan Ekonomi Lokal dan Pemberdayaan Masyarakat: Studi Kualitatif Kontribusi BMT Raudhah dalam Mendorong Pertumbuhan Ekonomi dan Kesejahteraan Masyarakat Lokal - Nasution, Zulhasby Assidqy; Syakir, Ahmad; Yanti , Nursantri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the contribution of BMT Raudhah in promoting economic growth and the welfare of the local community. BMT Raudhah is one of the business units owned by the Ar-Raudhatul Hasanah Islamic Boarding School Cooperative in Medan. This study employs a qualitative method to explore the role of BMT Raudhah in fostering economic growth and community welfare. Data were collected through in-depth interviews with several BMT Raudhah administrators. The results indicate that BMT Raudhah significantly contributes to the economic development of its members by providing business capital, entrepreneurship training, and other support. Additionally, BMT Raudhah empowers the community by offering sharia-based services and products such as savings and deposits, which can help individuals achieve their welfare. Through its products based on Islamic values, BMT Raudhah is able to assist its members in driving economic growth and enhancing community wellbeing. This research is expected to provide theoretical and practical contributions to the development of BMTs, particularly in increasing their contributions to promoting economic growth and the welfare of local communities.